Pengaplikasian konsep contrapuntal sound melalui penyuntingan dalam filem pendek Jogan Andika / Muhammad Faidhi Abu Zaid - Abu Zaid, Muhammad Faidhi (Faculty of Education, 2013)
This mini thesis is purposefully brought into existence to show the exhibition of the application of one small study on the concept of contrapuntal sound by editing the short film Jogan Andika be produced by the artist. This mini thesis will touch on the application of editing technique and applying the concept that is used in the fore mentioned short film. This mini thesis is also done in order to reveal whether the director of the short film have any concrete or clear reasons to apply these editing techniques into his short film. With intellectual quotes from scholars of the field of film, it has become a basis to form such application by the artiste himself. The Action Research method is the dominant method that is used within this mini thesis